Invasive ectomycorrhizal fungi: belowground insights from South America - Policelli, Nahuel (2025)
Ectomycorrhizal fungi (EMF) are essential for nutrient cycling and plant symbiosis, yet theirinvasions remain understudied, particularly in South America. Large-scale forestry introductionshave spread non-native EMF across the continent. Although deﬁnitions vary, EMF are invasivewhen they disperse, colonize new environments, and overcome natural barriers. Invasive EMFalter soil biogeochemistry and local microbial and plant communities, sometimes preceding plantinvasions. Despite their importance, invasive EMF remain poorly documented, with majorknowledge gaps. Research must strengthen local networks, expand access to molecular tools,and integrate traditional knowledge. In turn, unregulated commercial inoculants pose risks,requiring policy intervention. South America offers a unique opportunity to strengthencollaboration and regional research to help elucidate and prevent future EMF invasions whileguiding conservation.